(untitled) (Revista Direitos Humanos e Democracia, 2024)
This study aims to address the contributions of community mediation to access to justice. To do so, it approaches the communitarian movement and its reflexes in the Judiciary; exposes the roots of community mediation in the world and in Brazil; and discusses access to justice and proper dispute resolution through community mediation. The deductive method was used, which allows reasoning from premises to reach a logically correct conclusion based on one or more arguments, while regarding the nature of the research, the qualitative approach was adopted, which was operationalized by the research of a bibliographic nature. . It was seen that community mediation is a practice that enables emancipation, considering that it awakens in the individual the ability he has to, by himself, recognize his rights, duties and manage them consciously. At the end of the study, it was concluded that Community Justice offers a series of benefits to local communities, among which are mentioned: approximation between the community and the judicial system; community empowerment and participation; faster and more efficient conflict resolution; reduced costs; strengthening of social ties; personalized and culturally sensitive solutions; and prevention of future conflicts. The effectiveness of community justice also depends on the collaboration and commitment of all involved, including community members, local leaders and judicial authorities. When properly implemented, this approach can bring significant benefits to communities, promoting greater equity, justice and social cohesion.